2017
DOI: 10.3390/ijfs6010002
|View full text |Cite
|
Sign up to set email alerts
|

An Econometric Analysis of ETF and ETF Futures in Financial and Energy Markets Using Generated Regressors

Abstract: Abstract:It is well known that there is an intrinsic link between the financial and energy sectors, which can be analysed through their spillover effects, which are measures of how the shocks to returns in different assets affect each other's subsequent volatility in both spot and futures markets. Financial derivatives, which are not only highly representative of the underlying indices, but can also be traded on both the spot and futures markets, include Exchange Traded Funds (ETFs), a tradable spot index whos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It also reported that the strength of the renewable power portfolios continues even with the advent and the recovery period of the COVID-19 crisis. The positive performance of renewable power portfolios is also documented in several academic research studies, such as those of Chang et al [4] and Chang et al [5]. These studies employed technical analysis and found superior returns for renewable energy stocks against fossil energy markets in the US and Europe.…”
Section: Introductionmentioning
confidence: 72%
“…It also reported that the strength of the renewable power portfolios continues even with the advent and the recovery period of the COVID-19 crisis. The positive performance of renewable power portfolios is also documented in several academic research studies, such as those of Chang et al [4] and Chang et al [5]. These studies employed technical analysis and found superior returns for renewable energy stocks against fossil energy markets in the US and Europe.…”
Section: Introductionmentioning
confidence: 72%
“…Existing literature [1] investigates the relationship between Financial ETF and Energy ETF, testing spillover effects among ETF and ETF futures and conducting empirical analysis for several sub-periods. Among others, they find that financial and Energy ETFs are suitable for constructing a financial portfolio from optimal risk management perspective.…”
Section: Energy Markets Development and Their Interplay With Financia...mentioning
confidence: 99%
“…The only exception is the analysis of the Asia-Pacific markets presented in Marszk et al (2019)-due to different geographical coverage, it cannot be compared directly to the current study. In the recent years, there have been a number of studies devoted to the relationships between ETFs and futures but they have focused on particular attributes of selected instruments rather than market-broad analysis (e.g., Liu and Tse 2017;Oztekin et al 2017;Chang et al 2018;Wang et al 2018;Chang et al 2019;Jiang et al 2019;Wallace et al 2019;Liu et al 2020).…”
Section: Introductionmentioning
confidence: 99%